The Influence of the Independent Board of Commissioners, Institutional Ownership and Managerial Ownership on Profit Management - Orbawan, Yodi; April, Sonni Tri Aries (Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to determine the influence of an independent board of commissioners, institutional ownership and managerial ownership on earnings management in various industrial and textile subsectors in 2018-2020. This type of research is quantitative research. The population in this research are various industrial and textile sector companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling used the perposive sampling method. The number of samples is 30. The sampling method uses the perposive sampling method. The number of samples is 30. The data collection method in this research is documentation. Using SPSS 25 data testing. The data analysis techniques used are descriptive statistics, classical assumption tests and T statistical tests. Independent Board of Commissioners has a positive and insignificant effect on earnings quality, institutional ownership has no significant effect on earnings quality, managerial ownership has an insignificant effect on earnings quality. Meanwhile, simultaneously the influence of the independent board of commissioners, institutional ownership and managerial ownership on earnings management has no effect. Keywords: board of commissioners, institutional ownership, managerial ownership, profit management